Effects of Lactic Acid Bacteria Isolated From Rumen Fluid and Feces of Dairy Cows on Fermentation Quality, Microbial Community, and in vitro Digestibility of Alfalfa Silage - Guo, Linna; Yao, Dandan; Li, Dongxia; Lin, Yanli; Bureenok, Smerjai; Ni, Kuikui; Yang, Fuyu (Frontiers in Microbiology, 2020)
The objective of this study was to select lactic acid bacteria (LAB) isolated from the rumen fluid and feces of dairy cows, and evaluate their effects on silage quality of alfalfa after 30 or 60 days of ensiling. One hundred and four LAB strains were isolated from rumen fluid and feces of 6 dairy cows, of which 4 strains (Lactobacillus plantarum F1, Lactobacillus plantarum F50, Lactobacillus salivarius L100, and Lactobacillus fermentum L120) and one commercial inoculant (GFG) isolated from forage were employed for further study. The silages treated with F1 had the lowest (P < 0.05) pH value and the highest (P < 0.05) lactic acid content in all treatments. Besides, higher (P < 0.05) in vitro digestibility was also observed in F1-treated silage after 60 days of ensiling. The microbial analysis showed that the Lactobacillus abundance in the F1-treated silages increased to 60.32%, higher than other treatments (5.12-47.64%). Our research indicated that strain F1 could be an alternative silage inoculant, and dairy cows could be a source for obtaining excellent LAB for ensiling.